SPOCK1 Promotes the Development of Hepatocellular Carcinoma - Váncza, Lóránd; Karászi, Katalin; Péterfia, Bálint; Turiák, Lilla; Dezső, Katalin; Sebestyén, Anna; Reszegi, Andrea; Petővári, Gábor; Kiss, András; Schaff, Zsuzsanna; Baghy, Kornélia; Kovalszky, Ilona (Frontiers in Oncology, 2022)
The extracellular matrix proteoglycan SPOCK1 is increasingly recognized as a contributor to the development and progression of cancers. Here we study how SPOCK1 that is present in nontumorous hepatocytes at low concentrations promotes the development and progression of malignant hepatocellular tumor. Although SPOCK1 is an extracellular matrix proteoglycan, its concentration increases in the cytoplasm of hepatocytes starting with very low expression in the normal cells, then appearing in much higher quantities in cells of cirrhotic human liver and hepatocellular carcinoma. This observation is similar to that to that observed after diethylnitrosamine induction of mouse hepatocarcinogenesis. Furthermore, syndecan-1, the major proteoglycan of the liver, and SPOCK1 are in inverse correlation in course of these events. In hepatoma cell lines the cytoplasmic SPOCK1 colocalized with mitochondrial markers, such as MitoTracker and TOMM20, a characteristic protein of the outer membrane of mitochondrion and could be detected in the cell nucleus. SPOCK1 downregulation of hepatoma cell lines by siRNA inhibited cell proliferation, upregulated p21, p27, and interfered with pAkt and CDK4 expression. A tyrosine kinase array revealed that inhibition of SPOCK1 in the liver cancer cells altered MAPK signaling and downregulated several members of Sarc family all related to the aggressivity of the hepatoma cell lines. These studies support the idea that SPOCK1 enhancement in the liver is an active contributor to human and rodent hepatocarcinogenesis and cancer progression. However, its mitochondrial localization raises the possibility, that it has a currently unidentified physiological function in normal hepatocytes.